2007
DOI: 10.1038/sj.bjc.6604129
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of EGFR, VEGF, and HER2 expression in cholangiocarcinoma

Abstract: Epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), and human epidermal growth factor receptor 2 (HER2) have been considered as potential therapeutic targets in cholangiocarcinoma, but no studies have yet clarified the clinicopathological or prognostic significance of these molecules. Immunohistochemical expression of these molecules was assessed retrospectively in 236 cases of cholangiocarcinoma, as well as associations between the expression of these molecules and clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
318
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(333 citation statements)
references
References 44 publications
12
318
1
2
Order By: Relevance
“…41 This may also hold true for cholangiocarcinoma, where EGFR was only positive in one case in contrast to that what has been reported in the literature. 42,43 Using the established morphological and immunohistochemical criteria for subtype classification of pancreatic intraductal papillary mucinous neoplasms, 6,31 we were able to classify the majority of intraductal papillary neoplasms of the bile duct (96%) as pancreato-biliary, intestinal, gastric or oncocytic subtype. This indicates that, as expected, intraductal papillary neoplasms of the bile duct share many similarities with pancreatic intraductal papillary mucinous neoplasms from the histological point of view.…”
Section: Discussionmentioning
confidence: 99%
“…41 This may also hold true for cholangiocarcinoma, where EGFR was only positive in one case in contrast to that what has been reported in the literature. 42,43 Using the established morphological and immunohistochemical criteria for subtype classification of pancreatic intraductal papillary mucinous neoplasms, 6,31 we were able to classify the majority of intraductal papillary neoplasms of the bile duct (96%) as pancreato-biliary, intestinal, gastric or oncocytic subtype. This indicates that, as expected, intraductal papillary neoplasms of the bile duct share many similarities with pancreatic intraductal papillary mucinous neoplasms from the histological point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression and sustained activation of EGFR are associated with tumor progression in biliary carcinoma (Yoon et al, 2004;Yoshikawa et al, 2008). In different types of cancer, EGFR activation disturbs cell-cell adhesion by destabilizing the E-cadherin/b-catenin complex, promotes epithelial-to-mesenchymal transition (EMT) and contributes to the acquisition of a motile phenotype (Henson and Gibson, 2006;Sebastian et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, VEGF upregulation in tumour cells is considered to be a mechanism of resistance to EGFR inhibitors (Viloria Petit et al, 2001). Earlier, we have also reported that EGFR and VEGF overexpressions are frequent in cholangiocarcinoma (B20 and 50%, respectively), that EGFR overexpression is an independent prognostic factor in IHCC, and that VEGF expression is associated with intrahepatic metastasis in IHCC (Yoshikawa et al, 2008). These observations prompted us to hypothesise that dual inhibition of both EGFR and VEGFR may exert a synergistic anti-tumour effect in cholangiocarcinoma.…”
mentioning
confidence: 99%